Complimentary split ring resonator sensor with high sensitivity based on material characterization - Amer Abbood Al-behadili; Teodor Petrescu; Iulia Andreea Mocanu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
A new model of microwave planar sensor established on the complementary split ring resonator (CSRR) as well as an air hole in substrate of the structure is introduced for a precise measurement of materials permittivity. The hole is filled into substrate of the planar microstrip line. The CSRR structure with hole is selected for the sensitivity analysis, the result is established to hold over quite sensitive compared with CSRR structure without hole and thus evidence to be more suitable for the sensor design. The sensor in the form of CSRRs operating at a 1.74–3.4 GHz band is explained. At resonance, it is found that the electric field produced straight the plane of CSRR being highly sensitive for the characterization of sample resident with the sensor. The minimum transmission frequency of sensor shifts from 3.4 to 1.74 GHz as the sample permittivity varies from 1 to 10. A numerical model is introduced here for the computation of the system resolution as a function of resonance frequency and sample permittivity using electromagnetic simulator. It is found that the proposed sensor provides 35% increment in sensitivity more than conventional sensor for same permittivity of the sample under test.